1993
DOI: 10.1007/bf00036093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pluronic F-68 on shoot regeneration from cultured jute cotyledons and on growth of transformed roots

Abstract: The effects have been studied of the non-ionic surfactant, Pluronic F-68, on the growth in culture of jute (Corchorus capsularis L.) cotyledons with attached petioles, cotyledon explants and transformed roots. Supplementation of culture medium with 0.001-0.5% (w/v) of either commercial grade Pluronic F-68 or a purified fraction prepared by passage through silica gel, stimulated shoot production from the petioles of C. capsularis var. D154 and C134 cotyledons. This effect was most marked in C134, because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
2
11
1
Order By: Relevance
“…The additional finding that supplementation of medium with Pluronic F-68 also suppressed the onset of necrosis in chrysanthemurn explants was consistent with previous findings using cultured, transformed roots of C. capsularis, where similar concentrations of the surfactant also suppressed necrosis and enabled the routine sub-culture period to be extended at least 10-fold (Khatun et al 1993). While the mechanism by which Pluronic inhibits the accumulation of polyphenolic compounds and, hence, necrosis has not been determined, the surfactant can alter the activity of key metabolic enzymes in cultured transformed roots of S. dulcamara (Kumar et al 1992).…”
Section: Treatmentsupporting
confidence: 78%
See 2 more Smart Citations
“…The additional finding that supplementation of medium with Pluronic F-68 also suppressed the onset of necrosis in chrysanthemurn explants was consistent with previous findings using cultured, transformed roots of C. capsularis, where similar concentrations of the surfactant also suppressed necrosis and enabled the routine sub-culture period to be extended at least 10-fold (Khatun et al 1993). While the mechanism by which Pluronic inhibits the accumulation of polyphenolic compounds and, hence, necrosis has not been determined, the surfactant can alter the activity of key metabolic enzymes in cultured transformed roots of S. dulcamara (Kumar et al 1992).…”
Section: Treatmentsupporting
confidence: 78%
“…The variation in the responses between the two chrysanthemum cultivars in the present investigation was also consistent with previous studies using this compound as a growth-enhancing medium supplement, where differences in response were seen not only between cells, tissues and organs from the same species, but also between species from different genera (Lowe et al 1993b). For example, culture of C. capsularis cotyledons with attached petioles in the presence of up to 0.5% (w/v) Pluronic F-68 increased shoot production, with no further stimulation at higher concentrations (Khatun et al 1993). In contrast, maximum growth of transformed roots of S. dulcamara occurred with 0.01% (w/v) Pluronic F-68 and that of leaf-derived callus with 0.1% (w/v) of the surfactant (Kumar et al 1992).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For successful genetic transformation, it is essential to have an efficient plant regeneration protocol from transformed cells or tissue through an in vitro culture method. There are a number of reports on in vitro regeneration of jute (Islam et al 1982, Ahmed et al 1989, Saha and Sen 1992, Seraj et al 1992, Khatun et al 1993, Saha et al 1999, Sarker et. al.…”
Section: Introductionmentioning
confidence: 99%
“…This same positive phenomenon was also seen in (i) yeast, due to an increase in cell permeability (Laouar et al, 1996); (ii) plant cells culture of Solatium dulcamara, by stimulation of root growth (Kumar et al, 1991;Khatun et al, 1993);and (iii) animal cells cultures of melanoma of hamsters and chick embryonic fibroblasts (Bentley et al, 1989). It has been suggested that the growth-promotion by Pluronic surfactants is a consequence of a mechanism which involves protection from mechanical damage (Handa-Corrigan et al, 1989) and/or an increase in nutrients uptake into cells (Cawrse et al, 1990;Mutwakil et al, 1997).…”
Section: Discussionmentioning
confidence: 63%